In Defense of Liberal-Pluralism : 2nd Edition. - Chidella, Upendra (Cambridge Scholars Publishing, 2015)
This book takes a critical view of Kantian and Neo-Kantian moral philosophers' preference of universalism, the unity of morality, moral impartiality, consensus, and common morality. The central claim of the book is if the human condition is treated as complex and infested with irreducible choices and alternatives, then moral rightness and wrongness ought to operate beyond these binaries; giving epistemic status to Pluralism's multiple rationalities. Redefining liberal-pluralism, the book also argues that moral reasoning is necessarily bound by paradoxes and contradictions, seen in our choices.